How Personalization Is Shaping Consumer Behavior : An Analysis of Data-Driven Marketing Trends - Anto Alson Raja A (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
The paper “How Personalization Is Shaping Consumer Behaviour: An Analysis of Data-Driven Marketing Trends” seeks to also analyse data mining in marketing and the extent to which personalization contributes to consumer behaviour. This relates to how with data and technology the use of Artificial Intelligence can replace and transform marketing and the ability for businesses to offer personalized experience. This means that through email marketers, consumer intimacy will be possible in some ways, which include but not limited to the following: product communication or advertisement. At the same time, the article raises questions, such as security of personal information and the benefits, which may be hazardous, resulting from constant request. The use of AI and machine Learning in personalization in marketing will grow stronger to improve the customers experience and meanwhile ensure a balanced and ethical approach.